2018
DOI: 10.2147/ott.s169155
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-regulated lncRNA CRPAT4 promotes cell migration via regulating AVL9 in clear cell renal cell carcinomas

Abstract: IntroductionLong noncoding RNAs (lncRNAs) are proven to be key regulators in cancer biology. Our screening effort for clear cell renal cell carcinoma (ccRCC) prognosis-associated lncRNAs identified a novel lncRNA, ccRCC prognosis-associated transcript 4 (CRPAT4), as one of the top candidates that was previously uncharacterized. The aim of this study was to verify the clinical significance of CRPAT4 in ccRCC patients and to explore its biological role as well as the underlying mechanisms, in ccRCC cell lines.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…5C; 2-0.16-1 ) functions in exocytic transport from the Golgi [83]. AVL9 knockdown resulted in abnormal mitoses associated with defective protein trafficking, and increased cell migration with development of cysts [84], but also reduced cell proliferation and migration in other studies [85]. Regardless, the yeast phenomic model together with pharmacogenomics data would predict that functional loss of AVL9 renders cells vulnerable to cytarabine.…”
Section: Resultsmentioning
confidence: 99%
“…5C; 2-0.16-1 ) functions in exocytic transport from the Golgi [83]. AVL9 knockdown resulted in abnormal mitoses associated with defective protein trafficking, and increased cell migration with development of cysts [84], but also reduced cell proliferation and migration in other studies [85]. Regardless, the yeast phenomic model together with pharmacogenomics data would predict that functional loss of AVL9 renders cells vulnerable to cytarabine.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al. revealed that under hypoxic conditions in ccRCC, lncRNA CRPAT4 promoted cell migration by regulating AVL9 ( 39 ). In the present study, we performed a co-expression analysis between hypoxia genes and differentially expressed lncRNAs through paired lncRNA and mRNA expression data in ccRCC patients from TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA PCGEM1 may be used as a scaffold to form a complex with HIF-1α and transcription factor Snail homolog 1 (SNAI1) and regulate the invasion and metastasis of gastric cancer cells (67). Hypoxia-induced lncRNA CRPAT4 is regulated by HIF-1α and plays a carcinogenic role by promoting the growth and migration of cancer cells (68). The presence of siRNA targeting HIF-1α may provide a novel direction for specific treatment against HIF-1α, and it could achieve molecular therapy by inducing apoptosis and increasing the sensitivity of radiotherapy (69,70).…”
Section: Role Of Hif-1 In Non-coding Rna Associated With Cscsmentioning
confidence: 99%